Reconciliation as practice of universality - Moos, Thorsten (Stellenbosch theological journal, 2024)
A new concept of reconciliation practices is developed by using the liberal theory of justice by John Rawls. In this perspective, reconciliation appears as a prerequisite of justice, denoting and rearraging the limits of any given community of justice. By drawing on examples in the fields of the restitution of looted art, the inclusion of handicapped people, religions in urban contexts and environmental ethics, practices of reconciliation are shown to be ambigous and incomplete in time, extent, depth and unconditionality. This observation leads to a theological interpretation of reconciliation as an eschatological concept that is proposed to interpret current major issues of justice and reconciliation.